2006
DOI: 10.1007/s00167-006-0168-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous patellar tendon avulsion fracture from both patella and tibial tuberosity: a case report

Abstract: We present a simultaneous patella tendon avulsion fracture from both sides of its attachment in an ectopic ossified patellar tendon. Medially two thirds of the patellar tendon was detached from the inferior patella, and laterally one third of that from anterior tibial tuberosity with the patellar tendon split. Osteosynthesis was used to restore the extensor mechanism of the knee. The result at 46 months was good, even though there were some remaining ectopic ossifications in the patellar tendon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Intraoperatively it was found that the fracture ran through the ossified patellar tendon similar to the description in the case report by Yoon et al 5. The weakest area is the junction between the ossified part and patella bone which ruptures on eccentric loading 5…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Intraoperatively it was found that the fracture ran through the ossified patellar tendon similar to the description in the case report by Yoon et al 5. The weakest area is the junction between the ossified part and patella bone which ruptures on eccentric loading 5…”
Section: Discussionsupporting
confidence: 74%
“…Ectopic ossification in patellar tendon is often observed close to the tibial tuberosity in Osgood-Schlatter’s disease, small areas distal to the inferior pole of patella in Jumpers knee and in more extensive form in patella alta of an injured knee 5. Intraoperatively it was found that the fracture ran through the ossified patellar tendon similar to the description in the case report by Yoon et al 5. The weakest area is the junction between the ossified part and patella bone which ruptures on eccentric loading 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] who described a case in which the ossified tendon ruptured in a z-like fashion from the proximal medial aspect to the distal lateral aspect. This differs from our patient's condition in that he had a prior partial patellectomy and the ossified tendon avulsed completely from its insertion into the tibial tubercle alone.…”
Section: Discussionmentioning
confidence: 99%
“…11 Two adult cases have also been reported; a 72 year old male with bipolar avulsion of an ectopically ossified patellar tendon in an arthritic knee following a twisting injury 3 and a 90 year old diabetic female with concurrent inferior third patellar fracture and anterior tibial tuberosity fracture following a fall. 17 Diagnosis of avulsion fracture of the tibial tuberosity with associated patellar ligament avulsion requires an accurate history, thorough physical examination and appropriate imaging. To aid diagnosis, Frankl et al 4 recommended using plain lateral knee radiographs in extension and flexion, with an increased patellar to tibial distance in flexion indicating a combined injury.…”
Section: [ ( ) T D $ F I G ]mentioning
confidence: 99%